Ethnoecology for the control of Hovenia dulcis in the deciduous seasonal forest Santa Catarina, Brazil - Silva, Karine Petter da; Novicki, Carolina; Santos, Karine Louise dos; Tavela, Alexandre de Oliveira (Ethnobotany Research and Applications, 2022)
Background: The Deciduous Seasonal Forest (DSF) is one of the most abundant phytophysiognomies in Santa Catarina State / Brasil. However, it is severely impacted by fragmentation and introduction of invasive exotic species. In this scenario, the Hovenia dulcis is a species with a high degree of biological invasion, including in protected areas as the Fritz Plaumann State Park/Santa Catarina. Our objective was to understand the history of introduction of this invasive species in the park area, as well as to identify plant species with the potential to replace H. dulcis. Methods: Semi-structured interviews were carried out with informants residing in the Park's Buffer Zone (BZ). As base data for analysis, we use citations of use and the potential replacement species. For the complementary analysis, the consensus value or level of fidelity for the uses was estimated. To investigate the introduction history of the species in the study region, a literature search was conducted on the use of H. dulces. Results: Twenty-four informants were interviewed. The uses related to H. dulcis comprised thirteen citations. In the analysis of rapid ordering, firewood (23.25) was the most cited use. A total of thirty-four cited species with the potential to replace H. dulcis was obtained. The species' introduction history confirmed the technical indication as one of the main stimulators of the species' expansion in the region. Conclusions: Results demonstrate that the species is considered, by farmers, technically suitable for cultivation in the BZ of the Park. Hence the importance of highlighting other species with a greater or equal level of biological characteristics to replace H. dulcis. Keywords: Invasive alien species; ethnobotany, protected areas Resumo Antecedentes: A Floresta Estacional Decidual (DSF) é uma das fitofisionomias mais abundante no Estado de Santa Catarina/Brasil. Contudo, é severamente afetada pela fragmentação e introdução de espécies exóticas invasoras. Neste cenário, a Hovenia dulcis é uma espécie com um alto grau de invasão biológica, inclusive em áreas protegidas como o Parque Estadual Fritz Plaumann/Santa Catarina. O nosso objetivo foi compreender a história da introdução desta espécie invasora na área do parque, bem como identificar espécies vegetais com potencial para substitui-la. Métodos: Foram realizadas entrevistas semi-estruturadas com informantes residentes na Zona de Amortecimento do Parque (ZA). Como dados de base para as análises utilizamos citações de uso e de espécies com potencial de substituição. Para a análise complementar, foi estimado o valor consensual ou o nível de fidelidade para os usos. Para investigar o histórico de introdução da espécie na região de estudo, foi conduzida busca bibliográfica sobre o uso da H. dulces. Resultados: Foram entrevistados vinte e quatro informantes. Os usos relacionados com H. dulcis compreenderam treze citações. Na análise de ordenamento rápido, a lenha (23,25) foi a utilização mais citada. Foi obtido um total de trinta e quatro espécies citadas com potencial para substituir a H. dulcis. A história de introdução da espécie confirmou a indicação técnica como um dos principais estimuladores da expansão da espécie na região. Conclusões: Os resultados demonstram que a espécie é considerada, pelo agricultores, tecnicamente adequada para o cultivo na ZA do Parque. Daí a importância de destacar outras espécies com maior ou igual nível de características biológicas desejáveis para substituir H. dulcis. Palavras chave: Espécies exóticas invasoras; etnobotânica, áreas protegidas